Identification of RNA-Tis11b complexes in activated B cells. - Tang, Ngang Heok. (2010)
RNA-binding proteins (RBPs) play important roles in regulating gene expression at post-transcriptional level. A type of RBPs, called 12-O-tetradecanoylphorbol-13-acetate (TPA) inducible sequence (TIS11) family members (Tis11, Tis11b and Tis11d), can bind to AU-rich elements (AREs) in 3’-untranslated region (3’ UTR) of mRNAs. To date, not much is known about roles of Tis11 family members in B and T lymphocytes and the full spectrum of their RNA targets in these cells has not been described. To address these issues, specific antibodies for each Tis11 family member must be identified. In this work, we identified a Tis11b-specific antibody, SB1/56.6, using Western blotting and immunoprecipitation in HEK 293T cells transiently expressing mTis11b constructs. Accumulation of Tis11b proteins in lipopolysaccharide (LPS)-induced activated splenic B cells was observed using this antibody. This antibody also showed good ability to immunoprecipitate Tis11b in LPS-induced activated B cells. Our data suggest that Tis11b may play a role during B cell activation processes and SB1/56.6 antibody could be used in cross-linking immunoprecipitation (CLIP) experiment to identify full spectrum of RNA targets of Tis11b. Therefore, a CLIP experiment for Tis11b was performed using SB1/56.6 antibody but no band corresponding to RNA-Tis11b complexes in LPS-induced activated B cells was observed.